Interpretação simultânea do Português para a Libras no Programa Roda Vida da TV Cultura - Nascimento, Nicolas (Universidade Federal de São Carlos, 2021)
A strong presence of Libras [Brazilian Sign Language] translation and interpretation in the audiovisual sector has grown over the years. The Law 10.436/02 (Libras – Brazilian Sign Language Law) (BRASIL, 2002), Decree 5.296 / 04 (BRASIL, 2004) and Decree 5.626/05 (BRASIL, 2005) are some of the documents responsible for the growing presence sign language translators/interpreters in the audiovisual area, as they ensure that the deaf person has access to the information being transmitted, such as subtitles for the deaf and the Libras window. The Associação Brasileira de Normas Técnicas (ABNT) [Brazilian Association of Technical Standards], in legal regulation NBR 15.290/05 – Acessibilidade em Comunicação na Televisão [Accessibility in Communication on Television] - stipulates rules and conditions for translation and interpretation to occur. The ABNT standard also entitles the space in which the translation and/or interpretation is conveyed as “Janela de Libras”. These documents have reflected in the forms of production of the Brazilian audiovisual culture considering that, due to the legislation, “Janela de Libras” has been inserted in different political, cinematographic and television productions. Confronted with that, this research has the general objective of investigating the process of intermodal interpretation of Portuguese for Libras carried out from the genre collective interview. The corpus was collected on TV Cultura, which shows the Roda Viva Program, with interpretation for Libras live on TV and Internet. The methodological device used was self-confrontation, simple and crossed, proposed in the context of the French Activity Clinic to investigate the relationship of the worker with the activity itself. From this study, different aspects of interpretation and strategies were found that are directly related to the investigated genre in question, namely (i) previous and complementary studies, (ii) the influence of time, (iii) Linguistic-Discursive strategies related to Libras parameters, (iv) professional dramatics in relation to interpretive choices and (v) the maintenance of interpretation strategies. Through the information obtained using self-confrontation, the initial questions were answered, as we found several characteristics related to this genre in particular, such as the need for a previous study for possible complementations, the constant concern with time and its influence on the process of taking decisions, the dramas of the work activity impact the professionals in a decision situation, the constant teamwork and the harmony between the interpreters who aim to achieve the best possible product for that circumstance. It is expected that this research will contribute to the practice of Libras interpreters and translators in audiovisual contexts, as well as to the training process of these professionals at different levels and spaces.
Simultaneous interpretation from Portuguese into Brazilian Sign Language on Roda Viva Program of TV Cultura
Keywords: Libras; tradução e interpretação audiovisual; Janela de Libras; interpretação televisiva; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::LINGUISTICA APLICADA